2016
DOI: 10.1589/jpts.28.3227
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effects of mirror therapy in children with cerebral palsy

Abstract: [Purpose] To provide data for systematic intervention plans in occupational therapy practice by objectivity showing the value of mirror therapy interventions in children with cerebral palsy. [Subjects and Methods] Medline and EMBASE databases were searched for the key words “cerebral palsy,” “mirror movement,” “mirror therapy,” and “mirror visual feedback.” Nine studies that met the inclusion and exclusion criteria were identified. The qualitatively determined level of evidence, period of research, comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
8
0
5
Order By: Relevance
“…In the present included studies, computerized or robotic sessions occurred mainly 5/weeks during 30 minutes (see Results/Type of intervention). However, standard mirror therapy sessions are also frequent [ 4 , 5 ]. In addition, the greater effect of robotic or virtual reality rehabilitation rather than conventional rehabilitation is not sure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present included studies, computerized or robotic sessions occurred mainly 5/weeks during 30 minutes (see Results/Type of intervention). However, standard mirror therapy sessions are also frequent [ 4 , 5 ]. In addition, the greater effect of robotic or virtual reality rehabilitation rather than conventional rehabilitation is not sure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence of the effectiveness of first-generation mirror therapy for some indications [ 3 5 ]. Second-generation therapies are also more expensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the previous work, one can see the gains of the participants in this study (Figures 2, 3 and 4). A previous systematic review conducted on children and adolescents with spastic hemiplegic cerebral palsy declared that the MVF shows a promising therapeutic effect on hand function [20,21]. In addition, Grunt et al [22] found that subjects with spastic hemiplegic cerebral palsy gained benefit from MVF by evaluating neurophysiological evidence that showed a significant increase in the excitability of primary motor cortex, following the application of MVF in children and adolescents with hemiparesis.…”
Section: Discussionmentioning
confidence: 99%